Longitudinal Evaluation of Noninvasive Biomarkers for Eosinophilic Esophagitis. Issue 2 (February 2017) - Min, Steve B.; Nylund, Cade M.; Baker, Thomas P.; Ally, Mazer; Reinhardt, Brian; Chen, Yen-Ju; Nazareno, Luz; Moawad, Fouad J.
Abstract : Background: The diagnosis and management of eosinophilic esophagitis (EoE) often requires multiple endoscopies. Serum biomarkers can be elevated in EoE patients, but their clinical utility in diagnosis and assessing response to treatment is not well established. Goals: To evaluate serum biomarkers in EoE subjects compared with controls and assess longitudinally in response to treatment. Study: We conducted a prospective cohort study of children and adults undergoing esophagogastroduodenoscopy for suspected EoE. After completing an 8-week course of proton-pump inhibitor therapy, esophageal mucosal biopsies were obtained, as well as, serum analysis of absolute eosinophil count (AEC), eotaxin-3, eosinophil-derived neurotoxin (EDN), eosinophil cationic protein (ECP) and interleukin-5. Subjects with normal endoscopic and histologic findings constituted controls. Those meeting criteria for EoE underwent repeat esophagogastroduodenoscopy and biomarker measurements following treatment with topical steroids for 8 weeks. Results: Median levels of AEC (263.50 vs. 102 cu/mm, P< 0.001), ECP (26.98 vs. 5.20 ng/mL, P< 0.001) and EDN (31.70 vs. 14.18 ng/mL, P= 0.004) were significantly elevated in EoE subjects compared with controls and correlated with esophageal eosinophilia. Levels of AEC (odds ratio, 1.79; 95% confidence interval, 1.28-2.64) and ECP (odds ratio, 1.61; 95% confidence interval, 1.23-2.36) were associated with a diagnosis of EoE. Among the 5 biomarkers evaluated, only AEC significantly predicted esophageal eosinophilia following topical steroid therapy in EoE subjects ( P= 0.006). Conclusions: AEC, ECP, and EDN were higher in EoE subjects compared with controls and correlated with degree of esophageal eosinophilia. Furthermore, AEC predicted post-treatment eosinophilia, suggesting a potential role in monitoring EoE disease activity.